Evaluation of pedagogical leadership through the Vanderbilt Assessment of Leadership in Education (VAL-ED). Adaptation to the context of Higher Education in Spain - Palomino Fernández, José Manuel; Cáceres Reche, María del Pilar; Aznar Díaz, Inmaculada; Lara Lara, Fernando (Cogent Social Sciences, 2024)
Pedagogical leadership has been widely recognized as an essential factor in improving educational quality. Different studies point to it as the second most influential element in student performance and outcomes after teaching practice. Although the evaluation of principal leadership is an important tool that could help to find ways to improve the effectiveness of principal leadership, the design of such evaluation tools has always been a challenge. On the other hand, when we refer to pedagogical leadership in the context of Higher Education, we find that the limited number of studies suggests that research is still insufficient. Therefore there is a need to continue to deepen this field of research, which will allow us to further explore pedagogical leadership in Higher Education, providing results that will have an impact on the effectiveness of organizational development and its improvement in all dimensions of the institution, as well as on the performance and results of the students. This study aims to translate the Vanderbilt Assessment of Leadership in Education (VAL-ED) into Spanish and adapt it to the context of Higher Education so that we can have a reliable and effective evaluation instrument that not only allows us to continue to study pedagogical leadership in this educational stage, but also to be able to find areas for improvement, to improve both the results of the students and the Higher Education educational institutions themselves.
Keywords: academic leadership; Higher Education; quality assurance; educational research; assessment; Emerging; Scopus